Straight : constructions of heterosexuality in the cinema - Dixon, Wheeler W., 1950- (Albany : State University of New York Press, 2003)
Explores the ways that stereotypes of heterosexuality are portrayed and constructed in film.
Machine generated contents note: Ch. 1 Constructing Straightness -- Ch. 2 Breaks in the System -- Ch. 3 Performativity and Rupture -- Ch. 4 Commodification of Straightness.
Includes bibliographical references (pages 161)-179) and index.
Print version record.
JSTOR
Keywords: Man-woman relationships in motion pictures; Sex role in motion pictures; Masculinity in motion pictures; Relations entre hommes et femmes au cinéma.; Rôle selon le sexe au cinéma.; Masculinité au cinéma.; PERFORMING ARTS -- Film & Video -- Reference; Man-woman relationships in motion pictures; Masculinity in motion pictures; Sex role in motion pictures; Electronic book